1965
DOI: 10.1111/j.1423-0410.1965.tb04321.x
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Precipitating Antibodies after Multiple Pregnancies

Abstract: Summary157 sera from pregnant women have been examined and 2 precipitating antibodies with Ag specificity have been detected, one in the serum of a puerpera after the 7th delivery and one in the serum of a woman after the 6th delivery. Neither of the women had ever received a blood transfusion.Résumé157 sérums provenant de femmes enceintes ont été examinés et on a découvert parmi ces 157 sérums, 2 sérums contenant des anticorps précipitants, avec la spécificité Lp; 1 des sérums provenait d'une femme en couche,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1966
1966
1978
1978

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It therefore seemed likely that in LDL-incompatible pregnancies isoprecipitins might be formed by foetomaternal isoimmunization. DURWALD et al [29] in the course of a study of 157 sera obtained from pregnant multiparae (with at least 4 pregnancies) found in fact two LDL-isoprecipitins with anti-Ag-specificity. One of these women was in her sixth pregnancy, the other in her seventh; none of them had ever had a transfusion.…”
Section: Formation and Properties Of The Group-speci$c Anti-ldl-antibmentioning
confidence: 99%
See 1 more Smart Citation
“…It therefore seemed likely that in LDL-incompatible pregnancies isoprecipitins might be formed by foetomaternal isoimmunization. DURWALD et al [29] in the course of a study of 157 sera obtained from pregnant multiparae (with at least 4 pregnancies) found in fact two LDL-isoprecipitins with anti-Ag-specificity. One of these women was in her sixth pregnancy, the other in her seventh; none of them had ever had a transfusion.…”
Section: Formation and Properties Of The Group-speci$c Anti-ldl-antibmentioning
confidence: 99%
“…BLUMBERG et al [20] subsequently made similar observations with respect t o factor Ag(b). BUNDSCHUH [23], DURWALD [29], as well as SPEISER and PAUSCH [47], demonstrated that Lp(a)-antigen is only very seldom detectable a t birth. In summary it can be said that in analogy to the haptoglobins and the immune globulins, the groupspecific antigen determinant LDL-fractions may often be absent at birth and that in most cases they develop slowly during infancy.…”
Section: Polymorphiams Of the Human Low-density Lipoproteinsmentioning
confidence: 99%
“…These leucoagglutinins are more frequent among women with erythrocyte antibodies. The antibodies against the Aga antigen of ALLISON and BLUMBERG seem t o be more frequent in multigravidae; they were found in 2 cases after 6 and 7 pregnancies among 157 multigravidae (DURWALD et al [2]). The frequency of the anti-Gm antibodies is very low among normal people (29 cases among 13000 blood donors); the frequency isincreased after multiple transfusions and specially with children with thalassemia [5] and also among patients with rheumatoid arthritis.…”
mentioning
confidence: 99%
“…These leucoagglutinins are more frequent among women with erythrocyte antibodies. The antibodies against the Aga antigen of ALLISON and BLUMBERG seem t o be more frequent in multigravidae; they were found in 2 cases after 6 and 7 pregnancies among 157 multigravidae (DURWALD et al [2]).…”
mentioning
confidence: 99%